Absence as an affordance: thinking with(out) water on the inland waterways. (January 2023) - Kaaristo, Maarja; Visentin, Francesco
This article extends our understanding of inland waterways by theorising the temporary absences of water in canals and rivers as possibilities for action, that is, affordances. The interplay of temporary absence and presence of water in the inland waterways provides a range of potentialities for various activities and practices. Affordance theory can help us to further theorise material absences and position them as important elements of performing, practicing and interpreting place. We show how temporary absence of water can create spatial, historical and communicative affordances, affording the movement of boats, revealing and recreating the past and raising environmental awareness. The paper is based on semi-ethnographic research on the rivers and canals in the United Kingdom and Italy, featuring document analysis, participant observation and semi-structured interviews with various waterway users.